Predictions for charged-hadron production in p-O collisions at LHC energies - Konrad, Luca; Schulz, Philipp; Wolschin, Georg (Physics letters, 2025)
We present predictions for centrality-dependent charged-hadron production in p-O collisions at top LHC energies based on a nonequilibrium-statistical relativistic diffusion model. Colour-glass condensate initial conditions are used in a three-sources momentum-space model for gluon-gluon, quark-gluon and gluon-quark sources. Our results are to be compared with forthcoming Run 3 pseudorapidity distributions for sNN=9.618 TeV p-O collisions.